(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Ethnobotanical information; Latex; Shivalik hills. DOI: 10.3329/bjpt.v17i1.5396 Bangladesh J. Plant Taxon. 17(1): 97-99, 2010 (June)